2021
DOI: 10.1007/s00259-021-05296-1
|View full text |Cite
|
Sign up to set email alerts
|

Prospective comparison of 18F-PSMA-1007 PET/CT, whole-body MRI and CT in primary nodal staging of unfavourable intermediate- and high-risk prostate cancer

Abstract: Purpose To prospectively compare 18F-prostate-specific membrane antigen (PSMA)-1007 positron emission tomography (PET)/CT, whole-body magnetic resonance imaging (WBMRI) including diffusion-weighted imaging (DWI) and standard computed tomography (CT), in primary nodal staging of prostate cancer (PCa). Methods Men with newly diagnosed unfavourable intermediate- or high-risk PCa prospectively underwent 18F-PSMA-1007 PET/CT, WBMRI with DWI and contrast-enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(58 citation statements)
references
References 27 publications
1
55
0
2
Order By: Relevance
“…PSMA PET has shown high accuracy in diagnosing and staging PCa, and is currently suggested by several international guidelines to investigate PCa in different clinical settings. [17][18][19][20] Several PSMA ligands for PET imaging are now available worldwide. Among them, 68 Ga-PSMA-11 has been approved by the American Food and Drug Administration.…”
Section: Discussionmentioning
confidence: 99%
“…PSMA PET has shown high accuracy in diagnosing and staging PCa, and is currently suggested by several international guidelines to investigate PCa in different clinical settings. [17][18][19][20] Several PSMA ligands for PET imaging are now available worldwide. Among them, 68 Ga-PSMA-11 has been approved by the American Food and Drug Administration.…”
Section: Discussionmentioning
confidence: 99%
“…PSMA PET/CT, WB-MRI and CT detected 87%, 45% and 26% of the lesions, respectively. At the patient level, the inter-reader agreement and concordance with histopathology findings were higher for PSMA PET-CT compared to those of WB-MRI and CT (kappa values of respectively 0.89 vs. 0.47 and 0.69, respectively [ 37 ]. Noteworthy, these authors also demonstrated that 74% of the metastatic lymph nodes were smaller than the anatomical cut-off size of 8 mm, confirming our previous report that 70% of PSMA PET-CT positive lymph nodes were presenting a size below 8 mm, with a smallest positive lesion size of 1.7 mm [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, they found that the node-based sensitivity increases to 81.7% and patient-based sensitivity to 85.9% when only LNs larger than 3 mm are included [ 124 ]. Considering multidisciplinary consensus as the standard, Malaspina et al showed significant superiority of [ 18 F]PSMA-1007 PET/CT over conventional imaging with patient-based sensitivity of 87% and specificity of 98% [ 125 ]. [ 18 F]FDCFPyL also showed the suboptimal sensitivity of 28.1–52.5% with excellent specificity of 94.0–99.4% for N-staging [ 126 , 127 ].…”
Section: Targeting Agentsmentioning
confidence: 99%